2021
DOI: 10.1002/ansa.202100052
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative age grading of mosquitoes using surface‐enhanced Raman spectroscopy

Abstract: Mosquito-borne pathogens, including malaria, Zika, dengue, and chikungunya continue to be a major public health concern globally. Based on the understanding that only older female mosquitoes are infectious and represent a risk to human health, scientists have sought to age-grade mosquitoes for decades. To date, however, no reliable, cost-effective and practical methods exist to age older mosquitoes despite the tremendous epidemiological value of this approach. This study is the first attempt to develop a surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Recently, Wang et al . (31) reported a study on mosquito age-grading that employed surface-enhanced Raman spectroscopy (SERS). To the best of our knowledge, Raman spectroscopy has not been used for mosquito taxonomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang et al . (31) reported a study on mosquito age-grading that employed surface-enhanced Raman spectroscopy (SERS). To the best of our knowledge, Raman spectroscopy has not been used for mosquito taxonomy.…”
Section: Introductionmentioning
confidence: 99%
“…These studies include analyses of the structure of honey bee wings (28), melanin in spiders (29), and bumble bees (30). Recently, Wang et al (31) reported a study on mosquito age-grading that employed surface-enhanced Raman spectroscopy (SERS). To the best of our knowledge, Raman spectroscopy has not been used for mosquito taxonomy.…”
Section: Introductionmentioning
confidence: 99%
“…The technique in current use for age grading is the Detinova parity method that assesses the age of a female mosquito by taking the changes in ovary appearance into account (Gray et al, 2022). In addition, novel tools like surfaceenhanced Raman spectroscopy (SERS) is currently being studied as a potential mosquito age grading technique (Wang D. et al, 2022). In a study by Wang et al, where age of a mosquito is determined by both SERS and Infrared spectroscopy states that key biological molecules are altered in a mosquito with age which subsequently alter the spectra obtained by either of the mentioned methods (Wang D. et al, 2022).…”
Section: Glutathione Metabolismmentioning
confidence: 99%
“…In addition, novel tools like surfaceenhanced Raman spectroscopy (SERS) is currently being studied as a potential mosquito age grading technique (Wang D. et al, 2022). In a study by Wang et al, where age of a mosquito is determined by both SERS and Infrared spectroscopy states that key biological molecules are altered in a mosquito with age which subsequently alter the spectra obtained by either of the mentioned methods (Wang D. et al, 2022). However, in the field, there is a lack of capacity to accurately determine the age of a mosquito caught in the wild.…”
Section: Glutathione Metabolismmentioning
confidence: 99%
“…Raman spectroscopy is emerging as a promising tool which can be further improved and tailored for the application of analyzing bacteria in a diverse range of fields including food safety, environmental monitoring, and clinical diagnosis 8–10 . It is a powerful analytical technique and has been widely used in the detection of chemical and biological components 11–13 . Raman spectroscopy is a form of vibrational spectroscopy which can be used to build an ultrasensitive platform when coupled with nanomaterials for molecular recognition ability and even single molecule detection 14 .…”
Section: Introductionmentioning
confidence: 99%